(untitled) (Bangladesh Journal of Botany, 2023)
Chromium, naturally present in trace amounts in the environment, poses a significant risk as both a carcinogen and a contaminant at elevated concentrations. The study explores the chromium accumulation potential of seven indigenous weeds of Hazaribagh, Bangladesh. It further investigates the threat and toxicity associated with vegetables, crops, and aromatic plant cultivation in chromium-laden soil. The study revealed that the study area contains alarmingly high levels of Cr (III), i.e., 2328–34,536 mg Cr/kg as demonstrated in a spatial GIS map. The weeds accumulated 27.8 – 2496.6 mg Cr/kg and 11.4 –506.9 mg Cr/kg in roots and shoots respectively. Among the seven weeds, Phyllanthus niruri, Cyperus sp., and Vernonia patula met at least one phytoremediation criteria and can be used for soil chromium remediation purposes. In the pot study, five species, Brassica nipus (mustard), Helianthus annuus (sunflower), Ocimum sanctum (holy basil), Capsicum annuum (green chili), and Abelmoschus esculentus (okra), were exposed to chromium (III) sulfate spiked soil for forty days at 100, 500, and 20000 mg Cr/kg soil concentrations. Green chili, sunflower, mustard, and okra demonstrated high chromium uptake in roots (13.3- 195 mg/ kg) and shoots (13.2-63.7 mg/kg) exceeding permissible and toxicity threshold for plants. These findings highlight the importance of not cultivating these species in chromium-contaminated areas. However, basil showed chromium tolerance by limiting the uptake in the shoot along with excellent growth reducing the risk of chromium transferring through the food chain, and therefore, is safe to grow in Hazaribagh for producing metal-free aromatic oil. Bangladesh J. Bot. 52(3): 875-882, 2023 (September)